If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2n + 4 Reorder the terms: 0 = 4 + 2n Solving 0 = 4 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 0 + -2n = 4 + 2n + -2n Remove the zero: -2n = 4 + 2n + -2n Combine like terms: 2n + -2n = 0 -2n = 4 + 0 -2n = 4 Divide each side by '-2'. n = -2 Simplifying n = -2
| n-2-9n=(-34) | | X-7=-13+x | | 1-6x=10+3x | | 6(h/5/7k) | | -5-5x=-15 | | -3(x+7)=4x | | 12y+10=10x | | 12(x+4)=3(4x+1)+45 | | =(2n-4)(n+1) | | 9x+38=10x | | 7x+8x=7+6 | | 4(3w-1)=20 | | -19=x-15 | | 8x^2+24x=7x^2-80 | | 5p+8=4p+15 | | 6x^2+3y=0 | | 2x-3+9=18 | | -7n=7 | | (2n-4)(n+1)= | | 4(4x-7)=39 | | a=b+2 | | 5(2x-7)-3=5(x-2)-18 | | 4z-19=-31+8z | | 10x-5(x-5)=5x+5 | | m=3v+6v | | 3x+3+4x-12+x=180 | | 7x-(8x+6)=6x-20 | | (2n-4)(4n+1)= | | x+2x-7=-3x+8 | | w/5+6=10 | | (5-9j)(5+9j)= | | m=3v+6 |